PEMBARUAN HUKUM ISLAM DALAM HUKUM KELUARGA DI INDONESIA - Mallarangan, Hilal (Hunafa: Jurnal Studia Islamika, 2008)
This article elaborates some aspects of reformation of the family law as the results ofÂ  the ijtihÃ¢d of Indonesian experts. Nevertheless, not all of their legal thoughts are described in this article except for the family law material that has become the positive law in Indonesia. In elaborating those aspects of reformation of the family law, the author employs a comparative analysis and a culture social and judicial approach. Having conducted a comparative analysis the author found that there were -at least- 12 items of modifications and of reformation of the Islamic family law in the Indonesian family law, both in marriage, inheritance, will and bequest.Kata Kunci: pembaruan hukum, hukum keluarga Islam